Perspektif Kinerja Dalam Manajemen Sumber Daya Manusia (Sebuah Refleksi Dari Hasil Penelitian Internal Bidang Manajemen) - Peny, Theresia Lounggina Luisa (Peneliti.net, 2025)
This paper is a summary of the journey of four (4) years of research conducted in the field of management science, specifically human resource management. This research was conducted in four different research locations with the aim of determining the extent to which employees' understanding of employee performance values ​​is absorbed from a management science perspective. The results of this 4-year research conclude that: There is an influence of Democratic Leadership and Organizational Culture on Employee Performance at the Alor Regency Tourism Office. The influence of Leadership and Organizational Culture on Employee Performance at the Alor Regency Tourism Office is 80.1% There is an influence of Work Discipline, Democratic Leadership and Organizational Culture on Employee Performance at the Alor Regency Regional Disaster Management Agency Office. The influence of Work Discipline, Democratic Leadership and Organizational Culture on Employee Performance at the Regional Disaster Management Agency Office of Alor Regency is 87.1% There is an influence of Work Discipline, Democratic Leadership and Organizational Culture on Employee Performance at the Mali Airport Management Unit (UPBU) Office of Alor Regency. The influence of Individual Characteristics, Work Discipline, and Organizational Culture on Employee Performance at the Mali Airport Management Unit (UPBU) Office of Alor Regency is 87.80%. There is an influence of Employee Competence, Work Motivation, Work Discipline together on Employee Job Satisfaction at the Meteorology, Climatology and Geophysics Agency (BMKG) Mali Meteorological Station - Alor Regency by 68.06% There is an influence of Employee Competence, Work Motivation, Work Discipline and Work Satisfaction together on Employee Performance at the Meteorology, Climatology and Geophysics Agency (BMKG) Mali Meteorological Station - Alor Regency by 83.2% The magnitude of the influence of Employee Competence, work motivation and work discipline on Employee Performance through Employee Job Satisfaction at the Meteorology, Climatology and Geophysics Agency, Mali Meteorological Station, Alor Regency is 72.46%